The distinctive capacities of plants: re‐thinking difference via invasive species. Issue 3 (15th December 2014) - Head, Lesley; Atchison, Jennifer; Phillips, Catherine
<x xml:space="preserve">Abstract</x> The lower status of plants relative to animals, one of the defining characteristics of Western thought, is under challenge from diverse research in botany, philosophy and the more‐than‐human social sciences including geography. Although the agency of plants is increasingly demonstrated, scholars have yet to fully respond, for plants, to Lulka's call to attend more carefully to the details of nonhuman difference (Lulka D 2009 The residual humanism of hybridity: retaining a sense of the earth Transactions of the Institute of British Geographers NS 34 378–93). This paper advances the concept of the shared capacities of plants, in order to take them seriously in their own terms, and to consider what that means for human–plant relations more generally. We identify four capacities illustrated through plant lives: distinctive materialities; moving independent of humans; sensing and communicating; and taking shape as flexible bodies. Together these provide a sense of plant worlds in which distinct but highly variable plant forms have their own lives, interacting with humans and others in contingent ways. As empirical illustration we explore the adversarial relationship between rubber vine (Cryptostegia grandiflora) and invasive plant managers in northern Australia. In this case biosecurity strategies are affected by and affecting of rubber vine, assembling plants (as individuals and collectives), feral and stock animals, fire and helicopters, human skills and legislation. Recognition of plant capacities challenges us to rethink several concepts often framed against a human norm, including agency, subjectivity and the ethics of killing.